Development of the “Rehcardicare” Application for Post-Coronary Rehabilitation Artery Bypass Graft for Improving Cardiac Endurance Through Resistance and Flexibility Training - Rinawati Rinawati; Lidia Silaban (CV. Inara, 2025)
Background: Coronary heart disease (CHD) is a heart abnormality caused by narrowing or obstruction of the coronary arteries supplying blood to the heart. Objective: This study aimed to investigate the development of the